2013
DOI: 10.1021/jp403835m
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Titanium Oxide Nanostructures with Graphene and Functionalized Graphene Nanoribbons: A DFT Study

Abstract: Graphene substrates are known to have randomly located functional groups on their surface, particularly at their edges, including carboxylate, carbonyl, epoxy, and alcohol functionalities. However, the detailed interactions of these graphene functionalities with metal oxide nanoclusters are unexplored. This work examined the interaction of titania nanostructures with both graphene and functionalized graphene nanoribbons (GNRs) using density functional theory (DFT) calculations. The interactions of TiO 2 (anata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 50 publications
7
44
0
Order By: Relevance
“…As to other curves in Figure B, the broad peak at 3407 cm −1 were invisible, which indicated the reduction of ‐OH in the hydrothermal reaction, and the substrate of composite changed into GN. A new broad peak corresponding to the Ti‐O‐C bond appeared at 600 to 800 cm −1 , indicating formation of the chemical interaction between GN and TiO 2 particles . Similar spectra pattern were observed for GNT1% to GNT15%, suggesting they had similar structure and properties.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…As to other curves in Figure B, the broad peak at 3407 cm −1 were invisible, which indicated the reduction of ‐OH in the hydrothermal reaction, and the substrate of composite changed into GN. A new broad peak corresponding to the Ti‐O‐C bond appeared at 600 to 800 cm −1 , indicating formation of the chemical interaction between GN and TiO 2 particles . Similar spectra pattern were observed for GNT1% to GNT15%, suggesting they had similar structure and properties.…”
Section: Resultssupporting
confidence: 59%
“…A new broad peak corresponding to the Ti-O-C bond appeared at 600 to 800 cm −1 , indicating formation of the chemical interaction between GN and TiO 2 particles. 46 Similar spectra pattern were observed for GNT1% to GNT15%, suggesting they had similar structure and properties. Particularly, GNT3% presented a highest intensity among all samples.…”
Section: Characterization Of Gnt Compositessupporting
confidence: 56%
“…Besides the g‐C 3 N 4 /graphene composites, the interface interaction and energy gaps of TiO 2 /graphene composites have also been widely investigated by the DFT calculations . For example, Li et al demonstrated that the hybrid graphene/anatase TiO 2 nanocomposites exhibited a notable charge transfer from graphene layer to anatase TiO 2 in the ground electronic state, leading to an excess of holes in the graphene layer.…”
Section: Design Rules Of Graphene‐based Composite Photocatalystsmentioning
confidence: 99%
“…Considerable research effort has been made to modify the properties of GNRs, such as the effect of width, 16,17 defects, 18 doping, 19 adsorption, 18,20 shape (F-terminated helical, 21 tri-wing 22 ) or edges 23, 24 on the electronic and magnetic properties of GNRs. Two prototype GNRs which have been extensively studied are the armchair-and zigzag-edged GNRs (AGNRs and ZGNRs).…”
Section: Introductionmentioning
confidence: 99%